IMPROVING SKILLS THROUGH THE APPLICATION OF LEARNING MEDIA USING THE POWTOON APPLICATION - Nahda Almas Ainiyah; Bunga Shafira (International Conference on Social and Islamic Studies, 2021)
Skill is an ability that already exists in human or is natural. Skills can be learned throughreason, ideas, thoughts, and supported by power in a creative sense in order to create, changeor make something more meaningful and valuable so that it can produce a valuable workresult. Skills are needed in today’s modern era. Improving skills is one of the most importantthings, but support our daily needs or at work. As in the scope of education, skills can be animportant factor in teaching and learning activities. Using creative teaching media will fosterand increase the spirit of learning for student. Learning media is one type of learning aid thatcan be used to facilitate the learning process. The purpose of writing this article is the authorwants to provide information that the PowToon application can be the one of the alternativesto make learning media more interest and creative. The PowToon application can help us tomake animated videos or writings to make them more attracting. The research method usedby the author is a qualitative description methodology by collecting data, reading, takingnotes and processing research materials.